Cross-talk between the CK2 and AKT signaling pathways in cancer. (May 2017) - Ruzzene, Maria; Bertacchini, Jessika; Toker, Alex; Marmiroli, Sandra
Abstract: CK2 and AKT display a high degree of cross-regulation of their respective functions, both directly, through physical interaction and phosphorylation, and indirectly, through an intense cross-talk of key downstream effectors, ultimately leading to sustained AKT activation. Being CK2 and AKT attractive targets for therapeutic intervention, here we would like to emphasize how AKT and CK2 might influence cell fate through their complex isoform-specific and contextual-dependent cross-talk, to the extent that such functional interplay should be considered when devising therapies that target one or both these key signaling kinases.